2019
DOI: 10.1371/journal.pone.0211908
|View full text |Cite|
|
Sign up to set email alerts
|

Analysis of Anasplatyrhynchos genome resequencing data reveals genetic signatures of artificial selection

Abstract: Three artificially selected duck populations (AS), higher lean meat ratios (LTPD), higher fat ratios (FTPD) and higher quality meat (CMD), have been developed in China, providing excellent populations for investigation of artificial selection effects. However, the genetic signatures of artificial selection are unclear. In this study, we sequenced the genome sequences of these three artificially selected populations and their ancestral population (mallard, M). We then compared the genome sequences between AS an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 57 publications
1
4
1
Order By: Relevance
“…These results indicated that the majority of the identified mutations were located in non-coding sequences (intergenic regions or intronic regions), and only a small proportion of them fell in exon sequence, showing that only very few variants along with duck genome could exert functional effects on protein function. Our results were consistent with those of Xu et al [8] in ducks and Carneiro et al in rabbits [6].…”
Section: A Number Of Variants Are Found In Duck Genomesupporting
confidence: 94%
See 3 more Smart Citations
“…These results indicated that the majority of the identified mutations were located in non-coding sequences (intergenic regions or intronic regions), and only a small proportion of them fell in exon sequence, showing that only very few variants along with duck genome could exert functional effects on protein function. Our results were consistent with those of Xu et al [8] in ducks and Carneiro et al in rabbits [6].…”
Section: A Number Of Variants Are Found In Duck Genomesupporting
confidence: 94%
“…Subsequently, the highquality data were mapped to the A. platyrhynchos genome (BGI_duck_1.0), resulting in an average mapping rate of 93.14% and an average coverage rate of 95.63% for each individual (Table 1). The average mapping rate of this study (93.14%) was higher compared with our previous report (89.71%) [8], indicating a better quality of sequencing data used in this study.…”
Section: A Number Of Variants Are Found In Duck Genomecontrasting
confidence: 70%
See 2 more Smart Citations
“…As a result, various genetic studies have been conducted to discover economically valuable genetic characteristics of duck breeds. For example, three duck breeds, which were artificially selected in China, were analyzed to identify the genetic features related to artificial selection based on whole-genome sequencing data [ 12 ]. Positively selected genes and differentially expressed genes involved with muscle growth and lipid deposition were identified by comparing native Pekin duck and Cherry Valley Pekin duck using whole-genome and transcriptome sequencing data [ 13 ].…”
Section: Introductionmentioning
confidence: 99%